A Case Study Of Governmental Accounting And Budgeting Reform At Local Authority In Indonesia: An Institutionalist Perspective - Djamhuri , Ali (2009)
Kajian kes interpretif ini adalah mengenai pembaharuan perakaunan kerajaan tempatan di Jawa Timur, Indonesia